Epidemiology and Anatomic Distribution of Colorectal Cancer in South Africa - Amer, Akrem (Department of Surgery, 2021)
Background: Colorectal cancer (CRC) is the 5th most common cancer in subSaharan Africa (SSA) and the 3rd most common cancer in Southern Africa. CRC characteristics in SSA, including anatomic distribution, are not well described. Objective: To describe patient characteristics and anatomic location of colorectal adenocarcinoma (CRC-AC) in South Africa. Design: This was a retrospective study of CRC using the South African National Cancer Registry from 2006-2011. Main Outcome Measures: Patient age, gender, racial/ethnic group, province, histology type, and tumour location. Results: 6146 patients were included in the analysis. Among patients with adenocarcinomas, the median age of presentation was 60 (interquartile range, 49-70) years. 1372 (25%) of patients were < 50 years and 2870 (52%) were male. There were 5498 (89%) cases of adenocarcinoma (AC). 1277 (26%) CRC-AC were right colonic lesions, 1214 (25%) were left colonic lesions, and 2404 (49%) lesions were located in the rectum. Patients ≥ 50 years at presentation (OR=1.29. p< 0.001) and from Limpopo province (OR=1.46, p=0.029) were more likely to have left colonic and rectal adenocarcinoma on multivariate analysis. Patients who were black (OR=1.67, p< 0.001), had right colonic lesions (OR=1.25, p=0.007), and were from Mpumalanga (OR=1.67, p=0.007), Limpopo (OR=1.60, p=0.002), or Northwest (OR=1.76, p=0.001), were significantly associated with early onset adenocarcinoma. Conclusion: CRC-AC in South Africa presents at an earlier age than in HICs, such as the US. Early-onset CRC is higher in black South Africans who live in Mpumalanga, Limpopo, and Northwest in comparison with other provinces. The majority of colorectal cancer were leftsided and rectal; thus screening flexible sigmoidoscopy should be considered. Further studies on the age-specific incidence and the genetics and epigenetics of CRC-AC in South Africa are needed.